Clear Away the Smoke and Mirrors of Value-Added - HARRIS, DOUGLAS N. (Phi Delta Kappan, 2010)
Current value-added models for teacher accountability are better than models based only on student achievement, but they have their weakness. They are subject to systematic and random error, as are all measures, and there are concerns about the tests used for the measurements. However, value-added models are better than the alternatives at the school level and perhaps for individual teachers and teacher teams. (Contains 1 figure.)